Celebrating Matthew’s Passion narrative - O'Loughlin, Thomas (Taylor & Francis, 2018)
Twice each year, on Palm Sunday and Good Friday, the reading of the gospel becomes visibly a liturgical event in its own right. On these occasions the dramatic reading with several voices may replace the solitary tone of the deacon/priest. Yet in most parishes this is not only a missed opportunity to do something which can enhance the whole celebration, but can become something counter productive to good communication. At the very least it can become a shambles of voices coming in off-cue, lines-lost, or confused mumbling (“Whose line is it?” “Whose that voice supposed to represent?”). At worst it can it can send hidden signals to the congregation about how we view the passion, the Jews, and the ministry of proclamation.